Implementasi Manajemen Waralaba Rumah Makan Wong Solo: Perspektif Etika Bisnis Islam - Fikri Reza (Jihbiz : Jurnal Ekonomi, Keuangan dan Perbankan Syariah, 2018)
This study aims to determine what the form of franchise management is and the obstacles to its implementation in the perspective of Islamic business ethics. Rumah Makan Wong Solo Malang, is a reflection of the successful food and beverage industry. Rumah Makan Wong Solo does food business which according to religious norms is also categorized according to Islamic religious norms. For Muslims, business is in accordance with religious principles, which are always measured by the values contained in the Koran and the Sunnah of the Prophet (Hadith). In Islam, business ethics is called morals. Therefore, doing business must fulfill the moral guidance as stated in the source of Islamic teachings itself.